Endoscopic Cryosurgery - Chizh, Nikolay A. (Problems of Cryobiology and Cryomedicine, 2017)
This literature review discusses some issues concerning the use of cryosurgical method in experimental and clinical endoscopic surgery. Considering the pathogenetic mechanisms of low temperature effect on biological structures we demonstrated here the advantages and disadvantages of cryosurgical method application in medical practice. Underpinned by the clinical research data a positive effect of cryosurgical approaches using endoscopic equipment was shown and the prospects for further endoscopic cryosurgery development were determined. Probl Cryobiol Cryomed 2017; 27(1): 03–18